Omental infarction: A rare cause of acute abdomen - Nayak, Samir Ranjan; Mukesh, Vegulla Venkata; Chowdary, Manikanata; Borugadda, P Vijaya Kumar (Indian Journal of Case Reports, 2019)
Omental infarction is an uncommon but important cause of acute abdominal pain, which frequently mimics other surgical presentations. Low incidence and non-specific presentation contribute to Omental infarction being misconstrued for appendicitis, peptic ulcer perforation, acute pancreatitis or mesenteric ischemia. Its etiology remains uncertain, predisposing factors include obesity, strenuous activity, trauma, and sometimes idiopathic. Its diagnosis has traditionally been one of exclusion, based on intraoperative and pathologic findings. Here, we report the case of idiopathic omental infarction in a 51-year-old male. We discuss the diagnosis of primary omental infarction as well as the role of conservative and surgical management.